Advances in Network-Embedded Management and Applications Proceedings of the First International Workshop on Network-Embedded Management and Applications - Clemm, Alexander; Wolter, Ralf (Springer US : Imprint: Springer, 2011)
The general trend of modern network devices towards greater intelligence and programmability is accelerating the development of systems that are increasingly autonomous and to a certain degree self-managing. Examples range from router scripting environments to fully programmable server blades. This has opened up a new field of computer science research, reflected in this new volume. This selection of contributions to the first ever international workshop on network-embedded management applications (NEMA) features six papers selected from submissions to the workshop, held in October 2010 at Niagara Falls, Canada. They represent a wide cross-section of the current work in this vital field of inquiry. Covering a diversity of perspectives, the volume's dual structure first of all examines the 'enablers' for NEMAs-the platforms, frameworks, and development environments which facilitate the evolution of network-embedded management and applications. The second section of the book covers network-embedded applications that might both empower and benefit from such enabling platforms. These papers cover topics ranging from deciding where to best place management control functions inside a network to a discussion of how multi-core hardware processors can be leveraged for traffic filtering applications. The section concludes with an analysis of a delay-tolerant network application in the context of the 'One Laptop per Child' program. There is a growing recognition that it is vital to make network operation and administration as easy as possible to contain operational expenses and cope with ever shorter control cycles. This volume provides researchers in the field with the very latest in current thinking.